Zarządzanie środowiskowe jako determinanta odpowiedzialności w biznesie - Rogala, Piotr (Envinromental Management as a Determining Factor of Responsibility in Business, 2005)
This article presents the considerations about relations between environmental management and Corporate Social Responsibility (CSR). On the basis of the genesis examination and basic rules of CSR the author expressed that environmental management is an inseparable part of Corporate Social Responsibility.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Gospodarka a Środowisko (3); 2005; nr 1075, s. 130-136